Isolation and Characterization of Sesquiterpenes from Stem Bark of Warburgia ugandensis Sprague - Teshome Gonfa Hordofa (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2020)
Warburgia ugandensis Sprague is one of the medicinal plants traditionally used to treat a number of diseases like asthma, cough, diarrhea, common cold, stomachache and toothache in Ethiopia. However, there is still insufficient information on the isolation and evaluation of bioactive compounds from this plant species. Extraction, purification and isolation of the stem bark of this plant by dichloromethane and chloroform as solvents afforded two sesquiterpenes; namely, WU-1 (ugandensidial) and WU-2 (cinnamolide-3β-acetate) respectively. The structural elucidations of these bioactive compounds were accomplished by using a variety of spectroscopic methods (IR, UV and NMR). The spectroscopic results compared with the reported data in the literature.